Nuclear Power Under the Prophetic Legal Paradigm - ., Nurjihad; .Agung Prabowo, Bagya; Fairuzzaman, Fahmi (KnE Social Sciences, 2023)
This paper aimed to discuss nuclear power under the prophetic legal paradigm. Discussions of nuclear power frequently concentrate solely on its use as a weapon. There are many advantages to nuclear power. To fully utilize its benefits, and prevent any negative uses, a solid and transparent legal framework is required. However, a simply written law may be insufficient because it is conceivable for the law to fall short of the ideal to which it aspires. As a result, both at the international and national levels of the government in Indonesia, it is vital to include religious principles in the law. The prophetic legal paradigm is thought to be the most suitable framework for legal studies that relate to religious beliefs. This analysis demonstrated that the Indonesian nuclear law framework must be updated. It is crucial to keep in mind that the state cannot merely create rules that have no intrinsic purpose - ultimately offering phony security and justice. Laws must consider principles that serve interests of the humanity, particularly in Indonesia. Transcendence, liberty, and humanization are three values that can be combined. This paradigm will lead to the establishment of nuclear law with prophetic dimensions, bringing about real security and justice. Keywords: Nuclear Power, Nuclear Law, Prophetic Law